PENGARUH RESIKO DAN KUALITAS MANAJEMEN TERHADAP RASIO PERMODALAN PADA BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sari, Antiek Puspita; Sudiyatno, Bambang (Jurnal Ilmiah Telaah Manajemen, 2015)
Capitalization in the banking industry plays a very important role because it serves as a buffeagainst the possibility of risks and indicators of bank soundness. The purpose of this study is analyze the effect of risk and quality of management on the level of capital in Banks listed on thIndonesia Stock Exchange. This research includes descriptive type of research that intends describe the facts on the object of research and test the hypothesis based on empirical da ( empirical research ) . The study used secondary data from Indonesia Stock Exchange ( BEI ) in thperiod 2007-2011. The study population is all banking companies listed on the BEI. The sampleused are 28 banking companies taken with purposive sampling technique. Data obtained froICMD and IDX. Data analysis technique using multiple regression analysis. The result of thresearch concludes that: ( 1 ) NPL risk and index value risk ( Zrisk ) have negative effect on capitaratio ( Capital Adequecy Ratio-CAR ) . The magnitude of the risk of non-performing loans and the risof credit value will cause the bank to establish a credit abolishment reserve, the formation of thcredit cancellation reserves will lead to a reduction in income that can be used as additioncapital, so the sufficiency of capital needs will be reduced ( 2 ) capital ratios. ( 3 ) The managemequality ratio of Net Interest Margin ( NIM ) , Liquid Asset to Total Deposite ( LASCF ) , and Equity Total Liabilities ( EQTL ) have no effect on capital ratios.Keywords: capital adequecy ratio, risk, quality management